(3GdHjGf aj abg GdTGaYis - (3jMji Hf SGde Hf CSYO Hf jMji, CHh GdMSjf GdYeQGfj,J (B558 (3g` s
(3ChdgG (B:s
(3cJGH GdfcGM s
(3BNQgG (B:s
(3BNQ HGH GdWdGb s
(3ef GdfSNI GdSGHbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B196s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B290 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdabg GdTGaYjs